In-vitro study of matrix metalloproteinases in decellularized extracellular matrix of bovine diaphragm - Singh, Himani; Kumar, Naveen; Sharma, A K; Kataria, Meena; Munjal, Ashok (The Indian Journal of Animal Sciences, 2011)
The present study was undertaken for the identification of matrix metalloproteinases (MMPs) in the extracts obtained from a multi-step detergent-enzymatic extraction process involving 2 types of anionic and non-ionic detergents from bovine diaphragm and their possible involvement in the degradation of these biological materials. Anionic biological detergents treated bovine diaphragm expressed no band in SDS-PAGE analysis but non-ionic treated bovine diaphragm expressed almost similar bands as that of untreated treated bovine diaphragm. In gelatin zymography, anionic treated biomaterial expressed a 25 KDa band of MMPs, but in non-treated and non-ionic treated bovine diaphragm no band of MMPs was expressed. Anionic detergents played an important role in the removal of cells from bovine diaphragm and increasing MMPs activity in biomaterials as compared to non-ionic detergents.